In time [videorecording (DVD)] - Niccol, Andrew; Niccol, Andrew; Niccol, Andrew; Timberlake, Justin, 1981-; Seyfried, Amanda; Murphy, Cillian, 1976-; Wilde, Olivia (20th Century Fox Home Entertainment, 2011)
In a future where people stop aging at 25, but are engineered to live only one more year, having the means to buy your way out of the situation is a shot at immortal youth. Here, Will Salas finds himself accused of murder and on the run with a hostage, a connection that becomes an important part of the way against the system.